Role of cytochrome P450 genotype in the steps toward personalized drug therapy - Cavallari LH; Jeong H; Bress A (Dove Medical Press, 2011)
Larisa H Cavallari1,2, Hyunyoung Jeong1,2, Adam Bress11Department of Pharmacy Practice, 2Department of Biopharmaceutical Sciences, College of Pharmacy, University of Illinois at Chicago, Chicago, IL, USAAbstract: Genetic polymorphism for cytochrome 450 (P450) enzymes leads to interindividual variability in the plasma concentrations of many drugs. In some cases, P450 genotype results in decreased enzyme activity and an increased risk for adverse drug effects. For example, individuals with the CYP2D6 loss-of-function genotype are at increased risk for ventricular arrhythmia if treated with usual does of thioridazine. In other cases, P450 genotype may influence the dose of a drug required to achieve a desired effect. This is the case with warfarin, with lower doses often necessary in carriers of a variant CYP2C9*2 or *3 allele to avoid supratherapeutic anticoagulation. When a prodrug, such as clopidogrel or codeine, must undergo hepatic biotransformation to its active form, a loss-of-function P450 genotype leads to reduced concentrations of the active drug and decreased drug efficacy. In contrast, patients with multiple CYP2D6 gene copies are at risk for opioid-related toxicity if treated with usual doses of codeine-containing analgesics. At least 25 drugs contain information in their US Food and Drug Administration-approved labeling regarding P450 genotype. The CYP2C9, CYP2C19, and CYP2D6 genes are the P450 genes most often cited. To date, integration of P450 genetic information into clinical decision making is limited. However, some institutions are beginning to embrace routine P450 genotyping to assist in the treatment of their patients. Genotyping for P450 variants may carry less risk for discrimination compared with genotyping for disease-associated variants. As such, P450 genotyping is likely to lead the way in the clinical implementation of pharmacogenomics. This review discusses variability in the CYP2C9, CYP2C19, and CYP2D6 genes and the implications of this for drug efficacy and safety.Keywords: cytochrome P450, polymorphism, allele, drug metabolism, genotype